Ambivalent Deconstructions of Gendered Use of Hedges in Conversational Text Included in English Textbook for Junior High School in Indonesia - Hutapea, Jesica Vanessa; Suwastini, Ni Komang Arie; Blangsinga, Gede Wisma Krisna Ari Aditya; Adnyani, Ni Luh Putu Sri; Hadisaputra, I Nyoman Pasek; Jayantini, I Gusti Agung Sri Rwa (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Hedges have been attributed as stereotypical women’s language, marking them as indirect, doubtful, and sensitive communicators. This study traces the effort to deconstruct this gendered use of hedges in conversational texts included in the ninth grade Junior High School EFL textbook. Following the model of interactive qualitative data analysis by Miles, Huberman, and Saldana (2014) with Coates's perspective on women and language, the study reveals that the book has shown deconstructive efforts in the stereotypical use of hedges as women’s language by assigning male characters uttered hedges in the conversational texts. However, this effort is weakened by the significantly higer frequency hedges used by female characters as compared to those by male characters. Besides, the assigning of masculine topics for male speakers and feminine topics for semale speaker cast ambivalence in this effort. These results call for more persistent and concious efforts to include more consistent deconstructions of gendered language in future English textbooks.